How Do High-Latitude Volcanic Eruptions Affect Climate? - Pausata, Francesco S. R. (Eos, 2015)
High-Latitude Volcanic Eruption Impacts on Climate: Filling the Gaps; Stockholm, Sweden, 5–7 November 2014

On the enigmatic similarity in Greenland δ18 O between the Oldest and Younger Dryas - Pausata, Francesco S. R.; Löfverström, Marcus (Geophysical Research Letters, 2015)
Abstract The last deglaciation (20.0–10.0 kyr B.P.) was punctuated by two major cooling events affecting the Northern Hemisphere: the Oldest Dryas (OD; 18.0–14.7 kyr B.P.) and the Younger Dryas (YD; 12.8–11.5 kyr B.P.). Greenland ice core δ 18 O temperature reconstructions suggest that the YD was as cold as the OD, despite a 50 ppmv increase in atmospheric CO 2 , while modeling studies suggest that the YD was approximately 4–5°C warmer than the OD. This discrepancy has been surmised to result from changes in the origin of the water vapor delivered to Greenland; however, this hypothesis has not been hitherto tested. Here we use an atmospheric circulation model with an embedded moisture‐tracing module to investigate atmospheric processes that may have been responsible for the similar δ 18 O values during the OD and YD. Our results show that the summer‐to‐winter precipitation ratio over central Greenland in the OD is twice as high as in the YD experiment, which shifts the δ 18 O signal toward warmer (summer) temperatures (enriched δ 18 O values and it accounts for ~45% of the expected YD‐OD δ 18 O difference). A change in the inversion (cloud) temperature relationship between the two climate states further contributes (~20%) to altering the δ 18 O‐temperature‐relation model. Our experiments also show a 7% decrease of δ 18 O‐depleted precipitation from distant regions (e.g., the Pacific Ocean) in the OD, hence further contributing (15–20%) in masking the actual temperature difference. All together, these changes provide a physical explanation for the ostensible similarity in the ice core δ 18 O temperature reconstructions in Greenland during OD and YD. , Key Points Precipitation seasonality and inversion temperature changes behind YD‐OD δ 18 O enigma Local processes changes accounting up to 65% of the expected YD‐OD δ 18 O difference Moisture transport changes from the Pacific accounting only up to 20% of the expected YD‐OD δ 18 O difference

Tropical cyclone activity affected by volcanically induced ITCZ shifts - Pausata, Francesco S. R.; Camargo, Suzana J. (Proceedings of the National Academy of Sciences, 2019)
Significance Volcanic eruptions can inject a large amount of aerosol particles, which interact with solar radiation and consequently can affect the climate worldwide, hence the intensity and frequency of extreme events for a few years following the eruption. However, only a handful of studies have investigated the impacts of volcanic eruptions on tropical cyclone activity. Through a set of sensitivity modeling experiments, our study demonstrates that volcanic eruptions by shifting the Intertropical convergence zone can impact tropical cyclone activity up to 4 years following the eruption. These results will prove valuable to society, allowing us to better prepare for the consequences of changes in tropical cyclone activity following large volcanic eruptions. , Volcanic eruptions can affect global climate through changes in atmospheric and ocean circulation, and therefore could impact tropical cyclone (TC) activity. Here, we use ensemble simulations performed with an Earth System Model to investigate the impact of strong volcanic eruptions occurring in the tropical Northern (NH) and Southern (SH) Hemisphere on the large-scale environmental factors that affect TCs. Such eruptions cause a strong asymmetrical hemispheric cooling, either in the NH or SH, which shifts the Intertropical Convergence Zone (ITCZ) southward or northward, respectively. The ITCZ shift and the associated surface temperature anomalies then cause changes to the genesis potential indices and TC potential intensity. The effect of the volcanic eruptions on the ITCZ and hence on TC activity lasts for at least 4 years. Finally, our analysis suggests that volcanic eruptions do not lead to an overall global reduction in TC activity but rather a redistribution following the ITCZ movement. On the other hand, the volcanically induced changes in El Niño-Southern Oscillation (ENSO) or sea-surface temperature do not seem to have a significant impact on TC activity as previously suggested.

The sensitivity of the El Niño–Southern Oscillation to volcanic aerosol spatial distribution in the MPI Grand Ensemble - Ward, Benjamin; Pausata, Francesco S. R.; Maher, Nicola (Earth System Dynamics, 2021)
Abstract. Using the Max Planck Institute Grand Ensemble (MPI-GE) with 200 members for the historical simulation (1850–2005), we investigate the impact of the spatial distribution of volcanic aerosols on the El Niño–Southern Oscillation (ENSO) response. In particular, we select three eruptions (El Chichón, Agung and Pinatubo) in which the aerosol is respectively confined to the Northern Hemisphere, the Southern Hemisphere or equally distributed across the Equator. Our results show that relative ENSO anomalies start at the end of the year of the eruption and peak in the following one. We especially found that when the aerosol is located in the Northern Hemisphere or is symmetrically distributed, relative El Niño-like anomalies develop, while aerosol distribution confined to the Southern Hemisphere leads to a relative La Niña-like anomaly. Our results point to the volcanically induced displacement of the Intertropical Convergence Zone (ITCZ) as a key mechanism that drives the ENSO response, while suggesting that the other mechanisms (the ocean dynamical thermostat and the cooling of tropical northern Africa or the Maritime Continent) commonly invoked to explain the post-eruption ENSO response may be less important in our model.

How Will Sea Ice Loss Affect the Greenland Ice Sheet? - Pausata, Francesco S. R.; LeGrande, Allegra; Roberts, William (Eos, 2016)
On the Puzzling Features of Greenland Ice-Core Isotopic Composition; Copenhagen, Denmark, 26–28 October 2015

Deglacial Indian monsoon failure and North Atlantic stadials linked by Indian Ocean surface cooling - Tierney, Jessica E.; Pausata, Francesco S. R.; deMenocal, Peter (Nature Geoscience, 2016)

ENSO response to high‐latitude volcanic eruptions in the Northern Hemisphere: The role of the initial conditions - Pausata, Francesco S. R.; Karamperidou, Christina; Caballero, Rodrigo; Battisti, David S. (Geophysical Research Letters, 2016)
Abstract A large ensemble of Earth System Model simulations is analyzed to show that high‐latitude Northern Hemisphere eruptions give rise to El Niño‐like anomalies in the winter following the eruption, the amplitude of which depends on the state of the tropical Pacific at the time of the eruption. The El Niño‐like anomalies are almost three times larger when the eruption occurs during an incipient La Niña or during a neutral state compared to an incipient El Niño. The differential response results from stronger atmosphere‐ocean coupling and extra‐tropical feedbacks during an incipient La Niña compared to El Niño. Differences in the response continue through the second and third years following the eruption. When the eruption happens in a year of an incipient El Niño, a large cold (La Niña‐like) anomaly develops in year 2; if the eruption occurs in a year of an incipient La Niña, no anomalies are simulated in year 2 and a La Niña‐like response appears in year 3. After the El Niño‐like anomaly in the first winter, the overall tendency of ENSO in the following 2 years is toward a La Niña state. Our results highlight the high sensitivity of tropical Pacific dynamics under volcanic forcing to the ENSO initial state and lay the groundwork for improved predictions of the global climatic response to high‐latitude volcanic eruptions. , Key Points HL eruptions alter the mean state of ENSO, and detectable anomalies are seen up to 3 years after the eruption Stronger El Niño‐like anomalies on year 1 when eruptions occurs under developing La Niñas La Niña‐like anomalies on year 2 and year 3 when eruptions occurs under developing El Niños and La Niñas, respectively

Impacts of high-latitude volcanic eruptions on ENSO and AMOC - Pausata, Francesco S. R.; Chafik, Leon; Caballero, Rodrigo; Battisti, David S. (Proceedings of the National Academy of Sciences, 2015)
Significance In the model simulations analyzed here, large high-latitude volcanic eruptions have global and long-lasting effects on climate, altering the spatiotemporal characteristic of the El Niño–Southern Oscillation (ENSO) on both short (<1 y) and long timescales and affecting the strength of the Atlantic Meridional Overturning Circulation (AMOC). In the first 8–9 mo following the start of the eruption, El Niño-like anomalies develop over the equatorial Pacific. The large high-latitude eruptions also trigger a strengthening of the AMOC in the first 25 y after the eruption, which is associated with an increase in ENSO variability. This is then followed by a weakening of the AMOC lasting another 30–35 y, associated with decreased ENSO variability. , Large volcanic eruptions can have major impacts on global climate, affecting both atmospheric and ocean circulation through changes in atmospheric chemical composition and optical properties. The residence time of volcanic aerosol from strong eruptions is roughly 2–3 y. Attention has consequently focused on their short-term impacts, whereas the long-term, ocean-mediated response has not been well studied. Most studies have focused on tropical eruptions; high-latitude eruptions have drawn less attention because their impacts are thought to be merely hemispheric rather than global. No study to date has investigated the long-term effects of high-latitude eruptions. Here, we use a climate model to show that large summer high-latitude eruptions in the Northern Hemisphere cause strong hemispheric cooling, which could induce an El Niño-like anomaly, in the equatorial Pacific during the first 8–9 mo after the start of the eruption. The hemispherically asymmetric cooling shifts the Intertropical Convergence Zone southward, triggering a weakening of the trade winds over the western and central equatorial Pacific that favors the development of an El Niño-like anomaly. In the model used here, the specified high-latitude eruption also leads to a strengthening of the Atlantic Meridional Overturning Circulation (AMOC) in the first 25 y after the eruption, followed by a weakening lasting at least 35 y. The long-lived changes in the AMOC strength also alter the variability of the El Niño–Southern Oscillation (ENSO).

Rainfall regimes of the Green Sahara - Tierney, Jessica E.; Pausata, Francesco S. R.; deMenocal, Peter B. (Science Advances, 2017)
We estimate rainfall during the “Green Sahara” period. , During the “Green Sahara” period (11,000 to 5000 years before the present), the Sahara desert received high amounts of rainfall, supporting diverse vegetation, permanent lakes, and human populations. Our knowledge of rainfall rates and the spatiotemporal extent of wet conditions has suffered from a lack of continuous sedimentary records. We present a quantitative reconstruction of western Saharan precipitation derived from leaf wax isotopes in marine sediments. Our data indicate that the Green Sahara extended to 31°N and likely ended abruptly. We find evidence for a prolonged “pause” in Green Sahara conditions 8000 years ago, coincident with a temporary abandonment of occupational sites by Neolithic humans. The rainfall rates inferred from our data are best explained by strong vegetation and dust feedbacks; without these mechanisms, climate models systematically fail to reproduce the Green Sahara. This study suggests that accurate simulations of future climate change in the Sahara and Sahel will require improvements in our ability to simulate vegetation and dust feedbacks.

Robust Longitudinally Variable Responses of the ITCZ to a Myriad of Climate Forcings - Atwood, Alyssa R.; Donohoe, Aaron; Battisti, David S.; Liu, Xiaojuan; Pausata, Francesco S. R. (Geophysical Research Letters, 2020)
Abstract We evaluate the longitudinal variation in meridional shifts of the tropical rainbelt in response to natural and anthropogenic forcings using a large suite of coupled climate model simulations. We find that the energetic framework of the zonal mean Hadley cell is generally not useful for characterizing shifts of the rainbelt at regional scales, regardless of the characteristics of the forcing. Forcings with large hemispheric asymmetry such as extratropical volcanic forcing, meltwater forcing, and the Last Glacial Maximum give rise to robust zonal mean shifts of the rainbelt; however, the direction and magnitude of the shift vary strongly as a function of longitude. Even the Pacific rainband does not shift uniformly under any forcing considered. Forcings with weak hemispheric asymmetry such as CO 2 and mid‐Holocene forcing give rise to zonal mean shifts that are small or absent, but the rainbelt does shift regionally in coherent ways across models that may have important dynamical consequences. , Plain Language Summary A band of heavy precipitation spanning the deep tropics is an essential feature of the climate system that diverse ecosystems and billions of people depend on. It is well known that this rainbelt, when averaged across all longitudes, shifts north and south in response to heating or cooling the atmosphere in one hemisphere more than the other; this framework has been widely applied to study past tropical rainfall changes under differing climate states. However, we show using many different climate model experiments that this framework does not apply to regional shifts in the rainbelt. Changes in the rainbelt vary from place to place, and thus, data documenting north or south shifts in one location cannot be used to infer similar shifts at other longitudes. , Key Points The zonal mean ITCZ framework is generally not useful for characterizing regional shifts of the tropical rainbelt, regardless of the forcing Meridional shifts of the tropical rainbelt vary strongly with longitude under all forcings considered All forcings produce robust regional shifts in the rainbelt that are larger than (and sometime oppose the direction of) the zonal mean shift

Chinese stalagmite δ18O controlled by changes in the Indian monsoon during a simulated Heinrich event - Pausata, Francesco S. R.; Battisti, David S.; Nisancioglu, Kerim H.; Bitz, Cecilia M. (Nature Geoscience, 2011)

Revisiting the Mechanisms of ENSO Response to Tropical Volcanic Eruptions - Pausata, Francesco S. R.; Zhao, Yang; Zanchettin, Davide; Caballero, Rodrigo; Battisti, David S. (Geophysical Research Letters, 2023)
Abstract Stratospheric volcanic aerosol can have major impacts on global climate. Despite a consensus among studies on an El Niño‐like response in the first or second post‐eruption year, the mechanisms that trigger a change in the state of El Niño‐Southern Oscillation (ENSO) following volcanic eruptions are still debated. Here, we shed light on the processes that govern the ENSO response to tropical volcanic eruptions through a series of sensitivity experiments with an Earth System Model where a uniform stratospheric volcanic aerosol loading is imposed over different parts of the tropics. Three tropical mechanisms are tested: the “ocean dynamical thermostat” (ODT); the cooling of the Maritime Continent; and the cooling of tropical northern Africa (NAFR). We find that the NAFR mechanism plays the largest role, while the ODT mechanism is absent in our simulations as La Niña‐like rather than El‐Niño‐like conditions develop following a uniform radiative forcing over the equatorial Pacific. , Plain Language Summary Volcanic eruptions emit large quantity of sulfate aerosol up to the stratosphere. Such aerosol can alter global climate by interacting with solar radiation and in turn modifying atmospheric and ocean circulation. In particular, volcanic aerosol can alter the state of the El Niño‐Southern Oscillation (ENSO), the major mode of tropical climate variability. However, the mechanisms that trigger a change in the ENSO state following volcanic eruptions are still debated. In this study, we use an Earth System Model to revisit the main mechanisms that have been proposed to alter ENSO, causing positive temperature anomalies over the equatorial Pacific (EqPAC) Ocean. We tested three mechanisms: the “ocean dynamical thermostat” (ODT); the cooling of the Maritime Continent; and the cooling of tropical northern Africa (NAFR). Our experiments show that the NAFR mechanism plays the largest role, while the ODT mechanism is absent in our simulations as cold rather than warm develop over the EqPAC Ocean following the applied volcanic forcing. , Key Points Radiative cooling by volcanic aerosol over the tropical northern Africa triggers El Niño‐like conditions via atmospheric circulation changes The “ocean thermostat mechanism” is absent in our simulations when a uniform aerosol forcing is applied over the equatorial Pacific (EqPAC) The Maritime Continent cooling mechanism is not at play when the aerosol forcing extends over the entire EqPAC

ITCZ shift and extratropical teleconnections drive ENSO response to volcanic eruptions - Pausata, Francesco S. R.; Zanchettin, Davide; Karamperidou, Christina; Caballero, Rodrigo; Battisti, David S. (Science Advances, 2020)
Volcanic eruptions trigger ENSO response through shifts in the ITCZ and extratropical-to-tropical teleconnections. , The mechanisms through which volcanic eruptions affect the El Niño–Southern Oscillation (ENSO) state are still controversial. Previous studies have invoked direct radiative forcing, an ocean dynamical thermostat (ODT) mechanism, and shifts of the Intertropical Convergence Zone (ITCZ), among others, to explain the ENSO response to tropical eruptions. Here, these mechanisms are tested using ensemble simulations with an Earth system model in which volcanic aerosols from a Tambora-like eruption are confined either in the Northern or the Southern Hemisphere. We show that the primary drivers of the ENSO response are the shifts of the ITCZ together with extratropical circulation changes, which affect the tropics; the ODT mechanism does not operate in our simulations. Our study highlights the importance of initial conditions in the ENSO response to tropical volcanic eruptions and provides explanations for the predominance of posteruption El Niño events and for the occasional posteruption La Niña in observations and reconstructions.

Enhanced ice sheet melting driven by volcanic eruptions during the last deglaciation - Muschitiello, Francesco; Pausata, Francesco S. R.; Lea, James M.; Mair, Douglas W. F.; Wohlfarth, Barbara (Nature Communications, 2017)
Abstract Volcanic eruptions can impact the mass balance of ice sheets through changes in climate and the radiative properties of the ice. Yet, empirical evidence highlighting the sensitivity of ancient ice sheets to volcanism is scarce. Here we present an exceptionally well-dated annual glacial varve chronology recording the melting history of the Fennoscandian Ice Sheet at the end of the last deglaciation (∼13,200–12,000 years ago). Our data indicate that abrupt ice melting events coincide with volcanogenic aerosol emissions recorded in Greenland ice cores. We suggest that enhanced ice sheet runoff is primarily associated with albedo effects due to deposition of ash sourced from high-latitude volcanic eruptions. Climate and snowpack mass-balance simulations show evidence for enhanced ice sheet runoff under volcanically forced conditions despite atmospheric cooling. The sensitivity of past ice sheets to volcanic ashfall highlights the need for an accurate coupling between atmosphere and ice sheet components in climate models.

Climate effects of a hypothetical regional nuclear war: Sensitivity to emission duration and particle composition - Pausata, Francesco S. R.; Lindvall, Jenny; Ekman, Annica M. L.; Svensson, Gunilla (Earth's Future, 2016)
Abstract Here, we use a coupled atmospheric‐ocean‐aerosol model to investigate the plume development and climate effects of the smoke generated by fires following a regional nuclear war between emerging third‐world nuclear powers. We simulate a standard scenario where 5 Tg of black carbon ( BC ) is emitted over 1 day in the upper troposphere–lower stratosphere. However, it is likely that the emissions from the fires ignited by bomb detonations include a substantial amount of particulate organic matter ( POM ) and that they last more than 1 day. We therefore test the sensitivity of the aerosol plume and climate system to the BC / POM ratio (1:3, 1:9) and to the emission length (1 day, 1 week, 1 month). We find that in general, an emission length of 1 month substantially reduces the cooling compared to the 1‐day case, whereas taking into account POM emissions notably increases the cooling and the reduction of precipitation associated with the nuclear war during the first year following the detonation. Accounting for POM emissions increases the particle size in the short‐emission‐length scenarios (1 day/1 week), reducing the residence time of the injected particle. While the initial cooling is more intense when including POM emission, the long‐lasting effects, while still large, may be less extreme compared to the BC ‐only case. Our study highlights that the emission altitude reached by the plume is sensitive to both the particle type emitted by the fires and the emission duration. Consequently, the climate effects of a nuclear war are strongly dependent on these parameters. , Key Points Importance of including OC when simulating nuclear wars Importance of the fire emission length when simulating nuclear wars

Sources of Sahelian‐Sudan moisture: Insights from a moisture‐tracing atmospheric model - Salih, Abubakr A. M.; Zhang, Qiong; Pausata, Francesco S. R.; Tjernström, Michael (Journal of Geophysical Research: Atmospheres, 2016)
Abstract The summer rainfall across Sahelian‐Sudan is one of the main sources of water for agriculture, human, and animal needs. However, the rainfall is characterized by large interannual variability, which has attracted extensive scientific efforts to understand it. This study attempts to identify the source regions that contribute to the Sahelian‐Sudan moisture budget during July through September. We have used an atmospheric general circulation model with an embedded moisture‐tracing module (Community Atmosphere Model version 3), forced by observed (1979–2013) sea‐surface temperatures. The result suggests that about 40% of the moisture comes with the moisture flow associated with the seasonal migration of the Intertropical Convergence Zone (ITCZ) and originates from Guinea Coast, central Africa, and the Western Sahel. The Mediterranean Sea, Arabian Peninsula, and South Indian Ocean regions account for 10.2%, 8.1%, and 6.4%, respectively. Local evaporation and the rest of the globe supply the region with 20.3% and 13.2%, respectively. We also compared the result from this study to a previous analysis that used the Lagrangian model FLEXPART forced by ERA‐Interim. The two approaches differ when comparing individual regions, but are in better agreement when neighboring regions of similar atmospheric flow features are grouped together. Interannual variability with the rainfall over the region is highly correlated with contributions from regions that are associated with the ITCZ movement, which is in turn linked to the Atlantic Multidecadal Oscillation. Our result is expected to provide insights for the effort on seasonal forecasting of the rainy season over Sahelian Sudan. , Key Points The moisture associated with ITCZ flow accounts for about 40%‐50% of the precipitated water The local evaporation provides about 20% of the precipitated water The multiyear variability in the rainfall seems to be linked to the AMO

Effect of urban heat island mitigation strategies on precipitation and temperature in Montreal, Canada: Case studies - Lauer, Audrey; Pausata, Francesco S. R.; Leroyer, Sylvie; Argueso, Daniel (PLOS Climate, 2023)
High-resolution numerical weather prediction experiments using the Global Environmental Multiscale (GEM) model at a 250-m horizontal resolution are used to investigate the effect of the urban land-use on 2-m surface air temperature, thermal comfort, and rainfall over the Montreal (Canada) area. We focus on two different events of high temperatures lasting 2–3 days followed by intense rainfall: one is a large-scale synoptic system that crosses Montreal at night and the other is an afternoon squall line. Our model shows an overall good performance in adequately capturing the surface air temperature, dew-point temperature and rainfall during the events, although the precipitation pattern seems to be slightly blocked upwind of the city. Sensitivity experiments with different land use scenarios were conducted. Replacing all urban surfaces by low vegetation showed an increase of human comfort, lowering the heat index during the night between 2° and 6°C. Increasing the albedo of urban surfaces led to an improvement of comfort of up to 1°C during daytime, whereas adding street-level low vegetation had an improvement of comfort throughout the day of up to 0.5°C in the downtown area. With respect to precipitation, significant differences are only seen for the squall line event, for which removing the city modifies the precipitation pattern. For the large-scale synoptic system, the presence of the city does not seem to impact precipitation. These findings offer insight on the effects of urban morphology on the near-surface atmospheric conditions.

The water cycle of the mid‐Holocene West African monsoon: The role of vegetation and dust emission changes - Messori, Gabriele; Gaetani, Marco; Zhang, Qiang; Zhang, Qiong; Pausata, Francesco S. R. (International Journal of Climatology, 2019)
During the mid‐Holocene (6 kyr BP), West Africa experienced a much stronger and geographically extensive monsoon than in the present day. Changes in orbital forcing, vegetation and dust emissions from the Sahara have been identified as key factors driving this intensification. Here, we analyse how the timing, origin and convergence of moisture fluxes contributing to the monsoonal precipitation change under a range of scenarios: orbital forcing only; orbital and vegetation forcings (Green Sahara); orbital, vegetation and dust forcings (Green Sahara‐reduced dust). We further compare our results to a range of reconstructions of mid‐Holocene precipitation from palaeoclimate archives. In our simulations, the greening of the Sahara leads to a cyclonic water vapour flux anomaly over North Africa with an anomalous westerly flow bringing large amounts of moisture into the Sahel from the Atlantic Ocean. Changes in atmospheric dust under a vegetated Sahara shift the anomalous moisture advection pattern northwards, increasing both moisture convergence and precipitation recycling over the northern Sahel and Sahara and the associated precipitation during the boreal summer. During this season, under both the Green Sahara and Green Sahara‐reduced dust scenarios, local recycling in the Saharan domain exceeds that of the Sahel. This points to local recycling as an important factor modulating vegetation‐precipitation feedbacks and the impact of Saharan dust emissions. Our results also show that temperature and evapotranspiration over the Sahara in the mid‐Holocene are close to Sahelian pre‐industrial values. This suggests that pollen‐based paleoclimate reconstructions of precipitation during the Green Sahara period are likely not biased by possible large evapotranspiration changes in the region.

Understanding the Mechanisms behind the Northward Extension of the West African Monsoon during the Mid-Holocene - Gaetani, Marco; Messori, Gabriele; Zhang, Qiong; Flamant, Cyrille; Pausata, Francesco S. R. (Journal of Climate, 2017)
Abstract Understanding the West African monsoon (WAM) dynamics in the mid-Holocene (MH) is a crucial issue in climate modeling, because numerical models typically fail to reproduce the extensive precipitation suggested by proxy evidence. This discrepancy may be largely due to the assumption of both unrealistic land surface cover and atmospheric aerosol concentration. In this study, the MH environment is simulated in numerical experiments by imposing extensive vegetation over the Sahara and the consequent reduction in airborne dust concentration. A dramatic increase in precipitation is simulated across the whole of West Africa, up to the Mediterranean coast. This precipitation response is in better agreement with proxy data, in comparison with the case in which only changes in orbital forcing are considered. Results show a substantial modification of the monsoonal circulation, characterized by an intensification of large-scale deep convection through the entire Sahara, and a weakening and northward shift (~6.5°) of the African easterly jet. The greening of the Sahara also leads to a substantial reduction in the African easterly wave activity and associated precipitation. The reorganization of the regional atmospheric circulation is driven by the vegetation effect on radiative forcing and associated heat fluxes, with the reduction in dust concentration to enhance this response. The results for the WAM in the MH present important implications for understanding future climate scenarios in the region and in teleconnected areas, in the context of projected wetter conditions in West Africa.

High-latitude volcanic eruptions in the Norwegian Earth System Model: the effect of different initial conditions and of the ensemble size - Pausata, Francesco S. R.; Grini, Alf; Caballero, Rodrigo; Hannachi, Abdel; Seland, Øyvind (Tellus B: Chemical and Physical Meteorology, 2015)

Catastrophic Drought in the Afro-Asian Monsoon Region During Heinrich Event 1 - Stager, J. Curt; Ryves, David B.; Chase, Brian M.; Pausata, Francesco S. R. (Science, 2011)
An extreme megadrought occurred in the Afro-Asian monsoon region during an iceberg melting episode 50,000 years ago. , Between 15,000 and 18,000 years ago, large amounts of ice and meltwater entered the North Atlantic during Heinrich stadial 1. This caused substantial regional cooling, but major climatic impacts also occurred in the tropics. Here, we demonstrate that the height of this stadial, about 16,000 to 17,000 years ago (Heinrich event 1), coincided with one of the most extreme and widespread megadroughts of the past 50,000 years or more in the Afro-Asian monsoon region, with potentially serious consequences for Paleolithic cultures. Late Quaternary tropical drying commonly is attributed to southward drift of the intertropical convergence zone, but the broad geographic range of the Heinrich event 1 megadrought suggests that severe, systemic weakening of Afro-Asian rainfall systems also occurred, probably in response to sea surface cooling.

Causes of Past African Temperature Change in PMIP Simulations of the Mid‐Holocene - Marshall, Charlie; Morrill, Carrie; Dee, Sylvia; Pausata, Francesco S. R.; Russell, James (Paleoceanography and Paleoclimatology, 2024)
Abstract Current‐generation climate models project that Africa will warm by up to 5°C in the coming century, severely stressing African populations. Past and ongoing work indicates, however, that the models used to create these projections do not match proxy records of past temperature in Africa during the mid‐Holocene (MH), raising concerns that their future projections may house large uncertainties. Rather than reproducing proxy‐based reconstructions of MH warming relative to the Pre‐Industrial (PI), models instead simulate MH temperatures very similar to or slightly colder than the PI. This data‐model mismatch could be due to a variety of factors, including biases in model surface energy budgets or inaccurate representation of the feedbacks between temperature and hydrologic change during the “Green Sahara.” We focus on the differences among model simulations in the Paleoclimate Modeling Intercomparison Project Phases 3 and 4 (PMIP3 and PMIP4), examining surface temperature and energy budgets to investigate controls on temperature and the potential model sources of this paleoclimate data‐model mismatch. Our results suggest that colder conditions simulated by PMIP3 and PMIP4 models during the MH are in large part due to the joint impacts of feedback uncertainties in response to increased precipitation, a strengthened West African Monsoon (WAM) in the Sahel, and the Green Sahara. We extend these insights into suggestions for model physics and boundary condition changes, and discuss implications for the accuracy of future climate model projections over Africa. , Key Points We evaluate the simulation of African air temperatures in Paleoclimate Modeling Intercomparison Project Phases 3 and 4 simulations of the mid‐Holocene Energy balance decomposition analyses indicate the hydrologic cycle plays a key role in causing mid‐Holocene cooling in model simulations “Green Sahara” experiments show that dust and vegetation affect simulated temperatures, revealing pathways for refining model simulations

Unravelling the roles of orbital forcing and oceanic conditions on the mid-Holocene boreal summer monsoons - Mudra, Lekshmi; Sabin, T. P.; Krishnan, R.; Pausata, Francesco S. R.; Marti, Olivier; Braconnot, Pascale (Climate Dynamics, 2023)

Enhanced Himalayan Glacial Melting During YD and H1 Recorded in the Northern Bay of Bengal - Weldeab, Syee; Rühlemann, Carsten; Bookhagen, Bodo; Pausata, Francesco S. R.; Perez‐Lua, Fabiola M. (Geochemistry, Geophysics, Geosystems, 2019)
Abstract Ocean‐land thermal feedback mechanisms in the Indian Summer Monsoon (ISM) domain are an important but not well understood component of regional climate dynamics. Here we present a δ 18 O record analyzed in the mixed‐layer dwelling planktonic foraminifer Globigerinoides ruber ( sensu stricto ) from the northernmost Bay of Bengal (BoB). The δ 18 O time series provides a spatially integrated measure of monsoonal precipitation and Himalayan meltwater runoff into the northern BoB and reveals two brief episodes of anomalously low δ 18 O values between 16.3±0.4 and 16±0.5 and 12.6±0.4 and 12.3±0.4 thousand years before present. The timing of these events is centered at Heinrich event 1 and the Younger Dryas, well‐known phases of weak northern hemisphere monsoon systems. Numerical climate model experiments, simulating Heinrich event‐like conditions, suggest a surface warming over the monsoon‐dominated Himalaya and foreland in response to ISM weakening. Corroborating the simulation results, our analysis of published moraine exposure ages in the monsoon‐dominated Himalaya indicates enhanced glacier retreats that, considering age model uncertainties, coincide and overlap with the episodes of anomalously low δ 18 O values in the northernmost BoB. Our climate proxy and simulation results provide insights into past regional climate dynamics, suggesting reduced cloud cover, increased solar radiation, and air warming of the Himalaya and foreland areas and, as a result, glacier mass losses in response to weakened ISM. , Plain Language Summary Indian Summer Monsoon rainfall and Himalayan glacier/snow melts constitute the main water source for the densely populated Indian subcontinent. Better understanding of how future climate changes will affect the monsoon rainfall and Himalayan glaciers requires a long climate record. In this study, we create a 13,000‐year‐long climate record that allows us to better understand the response of Indian Summer Monsoon rainfall and Himalayan glaciers to past climate changes. The focus of our study is the time window between 9,000 and 22,000 years ago, an episode where the global climate experienced large and rapid changes. Our sediment record from the northern Bay of Bengal and climate change simulation indicate that during episodes of weak monsoon, the melting of the Himalayan glaciers increases substantially significantly. This is because the weakening of the monsoon results in less cloud cover and, as a result, the surface receives more sunlight and causes glacier melting. , Key Points Core sediments from the northern Bay of Bengal are a viable archive to reconstruct past changes in monsoonal and Himalayan meltwater runoff Weak monsoon reduces cloud cover and leads to increased radiative flux over the Himalaya and foreland areas and causes glacier mass loss A spatially integrated record of monsoon and Himalayan climate provides insights into regional climate dynamics

The role of the meridional sea surface temperature gradient in controlling the Caribbean low‐level jet - Maldonado, Tito; Rutgersson, Anna; Caballero, Rodrigo; Pausata, Francesco S. R.; Alfaro, Eric; Amador, Jorge (Journal of Geophysical Research: Atmospheres, 2017)
Abstract The Caribbean low‐level jet (CLLJ) is an important modulator of regional climate, especially precipitation, in the Caribbean and Central America. Previous work has inferred, due to their semiannual cycle, an association between CLLJ strength and meridional sea surface temperature (SST) gradients in the Caribbean Sea, suggesting that the SST gradients may control the intensity and vertical shear of the CLLJ. In addition, both the horizontal and vertical structure of the jet have been related to topographic effects via interaction with the mountains in Northern South America (NSA), including funneling effects and changes in the meridional geopotential gradient. Here we test these hypotheses, using an atmospheric general circulation model to perform a set of sensitivity experiments to examine the impact of both SST gradients and topography on the CLLJ. In one sensitivity experiment, we remove the meridional SST gradient over the Caribbean Sea and in the other, we flatten the mountains over NSA. Our results show that the SST gradient and topography have little or no impact on the jet intensity, vertical, and horizontal wind shears, contrary to previous works. However, our findings do not discount a possible one‐way coupling between the SST and the wind over the Caribbean Sea through friction force. We also examined an alternative approach based on barotropic instability to understand the CLLJ intensity, vertical, and horizontal wind shears. Our results show that the current hypothesis about the CLLJ must be reviewed in order to fully understand the atmospheric dynamics governing the Caribbean region. , Key Points Atmospheric dynamics in the Caribbean SST over the Caribbean Sea is examined as kinetic energy source for the CLLJ Impact of meridional SST gradient on the vertical structure of CLLJ

Atlantic hurricane response to Saharan greening and reduced dust emissions during the mid-Holocene - Dandoy, Samuel; Pausata, Francesco S. R.; Camargo, Suzana J.; Laprise, René; Winger, Katja; Emanuel, Kerry (Climate of the Past, 2021)
Abstract. We use a high-resolution regional climate model to investigate the changes in Atlantic tropical cyclone (TC) activity during the period of the mid-Holocene (MH: 6000 years BP) with a larger amplitude of the seasonal cycle relative to today. This period was characterized by increased boreal summer insolation over the Northern Hemisphere, a vegetated Sahara and reduced airborne dust concentrations. A set of sensitivity experiments was conducted in which solar insolation, vegetation and dust concentrations were changed in turn to disentangle their impacts on TC activity in the Atlantic Ocean. Results show that the greening of the Sahara and reduced dust loadings (MHGS+RD) lead to a larger increase in the number of Atlantic TCs (27 %) relative to the pre-industrial (PI) climate than the orbital forcing alone (MHPMIP; 9 %). The TC seasonality is also highly modified in the MH climate, showing a decrease in TC activity during the beginning of the hurricane season (June to August), with a shift of its maximum towards October and November in the MHGS+RD experiment relative to PI. MH experiments simulate stronger hurricanes compared to PI, similar to future projections. Moreover, they suggest longer-lasting cyclones relative to PI. Our results also show that changes in the African easterly waves are not relevant in altering the frequency and intensity of TCs, but they may shift the location of their genesis. This work highlights the importance of considering vegetation and dust changes over the Sahara region when investigating TC activity under a different climate state.

A 50-year cycle of sea surface temperature regulates decadal precipitation in the tropical and South Atlantic region - Gorenstein, Iuri; Wainer, Ilana; Pausata, Francesco S. R.; Prado, Luciana F.; Khodri, Myriam; Dias, Pedro L. Silva (Communications Earth & Environment, 2023)
Abstract Northeast Brazil and Western Africa are two regions geographically separated by the Atlantic Ocean, both home to vulnerable populations living in semi-arid areas. Atlantic Ocean modes of variability and their interactions with the atmosphere are the main drivers of decadal precipitation in these Atlantic Ocean coastal areas. How these low-frequency modes of variability evolve and interact with each other is key to understanding and predicting decadal precipitation. Here we use the Self-Organizing Maps neural network with different variables to unravel causality between the Atlantic modes of variability and their interactions with the atmosphere. Our study finds an 82% (p<0.05) anti-correlation between decadal rainfall in Northeast Brazil and Western Africa from 1979 to 2005. We also find three multi-decadal cycles: 1870-1920, 1920-1970, and 1970-2019 (satellite era), pointing to a 50-year periodicity governing the sea surface temperature anomalies of Tropical and South Atlantic. Our results demonstrate how Northeast Brazil and Western Africa rainfall anti-correlation was formed in the satellite era and how it might be part of a 50-year cycle from the Tropical and South Atlantic decadal variability.

The remote response of the South Asian Monsoon to reduced dust emissions and Sahara greening during the middle Holocene - Pausata, Francesco S. R.; Messori, Gabriele; Yun, Jayoung; Jalihal, Chetankumar A.; Bollasina, Massimo A.; Marchitto, Thomas M. (Climate of the Past, 2021)
Abstract. Previous studies based on multiple paleoclimate archives suggested a prominent intensification of the South Asian Monsoon (SAM) during the mid-Holocene (MH, ∼6000 years before present). The main forcing that contributed to this intensification is related to changes in the Earth's orbital parameters. Nonetheless, other key factors likely played important roles, including remote changes in vegetation cover and airborne dust emission. In particular, northern Africa also experienced much wetter conditions and a more mesic landscape than today during the MH (the so-called African Humid Period), leading to a large decrease in airborne dust globally. However, most modeling studies investigating the SAM changes during the Holocene overlooked the potential impacts of the vegetation and dust emission changes that took place over northern Africa. Here, we use a set of simulations for the MH climate, in which vegetation over the Sahara and reduced dust concentrations are considered. Our results show that SAM rainfall is strongly affected by Saharan vegetation and dust concentrations, with a large increase in particular over northwestern India and a lengthening of the monsoon season. We propose that this remote influence is mediated by anomalies in Indian Ocean sea surface temperatures and may have shaped the evolution of the SAM during the termination of the African Humid Period.

On the low-frequency variability of wintertime Euro-Atlantic planetary wave-breaking - Messori, Gabriele; Davini, Paolo; Alvarez-Castro, M. Carmen; Pausata, Francesco S. R.; Yiou, Pascal; Caballero, Rodrigo (Climate Dynamics, 2019)

Mid-Holocene climate at mid-latitudes: assessing the impact of Saharan greening - Gaetani, Marco; Messori, Gabriele; Pausata, Francesco S. R.; Tiwari, Shivangi; Alvarez Castro, M. Carmen; Zhang, Qiong (Climate of the Past, 2024)
Abstract. During the first half of the Holocene (11 000 to 5000 years ago), the Northern Hemisphere experienced a strengthening of the monsoonal regime, with climate reconstructions robustly suggesting a greening of the Sahara region. Palaeoclimate archives also show that this so-called African humid period (AHP) was accompanied by changes in climate conditions at middle to high latitudes. However, inconsistencies still exist in reconstructions of the mid-Holocene (MH) climate at mid-latitudes, and model simulations provide limited support in reducing these discrepancies. In this paper, a set of simulations performed using a climate model are used to investigate the hitherto unexplored impact of Saharan greening on mid-latitude atmospheric circulation during the MH. Numerical simulations show Saharan greening has a year-round impact on the main circulation features in the Northern Hemisphere, especially during boreal summer (when the African monsoon develops). Key findings include a westward shift in the global Walker Circulation, leading to modifications in the North Atlantic jet stream in summer and the North Pacific jet stream in winter. Furthermore, Saharan greening modifies atmospheric synoptic circulation over the North Atlantic, enhancing the effect of orbital forcing on the transition of the North Atlantic Oscillation phase from predominantly positive to negative in winter and summer. Although the prescription of vegetation in the Sahara does not improve the proxy–model agreement, this study provides the first constraint on the influence of Saharan greening on northern mid-latitudes, opening new opportunities for understanding MH climate anomalies in regions such as North America and Eurasia.

Greening of the Sahara suppressed ENSO activity during the mid-Holocene - Pausata, Francesco S. R.; Zhang, Qiong; Muschitiello, Francesco; Lu, Zhengyao; Chafik, Léon; Niedermeyer, Eva M.; Stager, J. Curt; Cobb, Kim M.; Liu, Zhengyu (Nature Communications, 2017)
Abstract The evolution of the El Niño-Southern Oscillation (ENSO) during the Holocene remains uncertain. In particular, a host of new paleoclimate records suggest that ENSO internal variability or other external forcings may have dwarfed the fairly modest ENSO response to precessional insolation changes simulated in climate models. Here, using fully coupled ocean-atmosphere model simulations, we show that accounting for a vegetated and less dusty Sahara during the mid-Holocene relative to preindustrial climate can reduce ENSO variability by 25%, more than twice the decrease obtained using orbital forcing alone. We identify changes in tropical Atlantic mean state and variability caused by the momentous strengthening of the West Africa Monsoon (WAM) as critical factors in amplifying ENSO’s response to insolation forcing through changes in the Walker circulation. Our results thus suggest that potential changes in the WAM due to anthropogenic warming may influence ENSO variability in the future as well.

Elevation-dependent intensification of fire danger in the western United States - Alizadeh, Mohammad Reza; Abatzoglou, John T.; Adamowski, Jan; Modaresi Rad, Arash; AghaKouchak, Amir; Pausata, Francesco S. R.; Sadegh, Mojtaba (Nature Communications, 2023)
Abstract Studies have identified elevation-dependent warming trends, but investigations of such trends in fire danger are absent in the literature. Here, we demonstrate that while there have been widespread increases in fire danger across the mountainous western US from 1979 to 2020, trends were most acute at high-elevation regions above 3000 m. The greatest increase in the number of days conducive to large fires occurred at 2500–3000 m, adding 63 critical fire danger days between 1979 and 2020. This includes 22 critical fire danger days occurring outside the warm season (May–September). Furthermore, our findings indicate increased elevational synchronization of fire danger in western US mountains, which can facilitate increased geographic opportunities for ignitions and fire spread that further complicate fire management operations. We hypothesize that several physical mechanisms underpinned the observed trends, including elevationally disparate impacts of earlier snowmelt, intensified land-atmosphere feedbacks, irrigation, and aerosols, in addition to widespread warming/drying.

Holocene forcing of East Asian hydroclimate recorded in a subtropical peatland from southeastern China - Huang, Xianyu; Zhang, Hongbin; Griffiths, Michael L.; Zhao, Bingyan; Pausata, Francesco S. R.; Tabor, Clay; Shu, Junwu; Xie, Shucheng (Climate Dynamics, 2023)

Northern Hemisphere Land Monsoon Precipitation Increased by the Green Sahara During Middle Holocene - Sun, Weiyi; Wang, Bin; Zhang, Qiong; Pausata, Francesco S. R.; Chen, Deliang; Lu, Guonian; Yan, Mi; Ning, Liang; Liu, Jian (Geophysical Research Letters, 2019)
Abstract Changes in land cover and dust emission may significantly influence the Northern Hemisphere land monsoon precipitation (NHLMP), but observations are too short to fully evaluate their impacts. The “Green Sahara” during the mid‐Holocene (6,000 years BP) provides an opportunity to unravel these mechanisms. Here we show that during the mid‐Holocene, most of the NHLMP changes revealed by proxy data are reproduced by the Earth System model results when the Saharan vegetation cover and dust reduction are taken into consideration. The simulated NHLMP significantly increases by 33.10% under the effect of the Green Sahara. The North African monsoon precipitation increases most significantly. Additionally, the Saharan vegetation (dust reduction under vegetated Sahara) alone remotely intensifies the Asian (North American) monsoon precipitation through large‐scale atmospheric circulation changes. These findings imply that future variations in land cover and dust emissions may appreciably influence the NHLMP. , Plain Language Summary Northern Hemisphere land monsoon precipitation (NHLMP) provides water resources for about two thirds of the world's population, which is vital for infrastructure planning, disaster mitigation, food security, and economic development. Changes in land cover and dust emissions may significantly influence the NHLMP, but observations are too short to understand the mechanisms. The Sahara Desert was once covered by vegetation and dust emission was substantially reduced during the mid‐Holocene (6,000 years BP), which provides an opportunity to test the models' capability and unravel these mechanisms. Here we use an Earth System model and find that when the Saharan vegetation and dust reduction are taken into consideration, the simulated annual mean precipitation over most of the NHLM regions shows a closer agreement with proxy records. The sensitivity experiments show that the North African monsoon precipitation increases most significantly under the regional effects of “Green Sahara.” The Saharan vegetation (dust reduction under vegetated Sahara) alone also remotely increases the Asian (North American) monsoon precipitation through large‐scale atmospheric circulation changes. The knowledge gained from this study is critical for improved understanding of the potential impacts of the land cover and dust changes on the projected future monsoon change. , Key Points The first study of the impact of Saharan vegetation and dust reduction on the NHLMP Comparison with proxy records shows the effect of the Green Sahara improves the simulated NHLMP The Saharan vegetation and dust reduction significantly increase the NHLMP by 33.10%

On the links between meteorological variables, aerosols, and tropical cyclone frequency in individual ocean basins - Chiacchio, Marc; Pausata, Francesco S. R.; Messori, Gabriele; Hannachi, Abdel; Chin, Mian; Önskog, Thomas; Ekman, Annica M. L.; Barrie, Leonard (Journal of Geophysical Research: Atmospheres, 2017)
Abstract A generalized linear model based on Poisson regression has been used to assess the impact of environmental variables modulating tropical cyclone frequency in six main cyclone development areas: the East Pacific, West Pacific, North Atlantic, North Indian, South Indian, and South Pacific. The analysis covers the period 1980–2009 and focuses on widely used meteorological parameters including wind shear, sea surface temperature, and relative humidity from different reanalyses as well as aerosol optical depth for different compounds simulated by the Goddard Chemistry Aerosol Radiation and Transport model. Circulation indices are also included. Cyclone frequency is obtained from the International Best Track Archive for Climate Stewardship. A strong link is found between cyclone frequency and the relative sea surface temperature, Atlantic Meridional Mode, and wind shear with significant explained log likelihoods in the North Atlantic of 37%, 27%, and 28%, respectively. A significant impact of black carbon and organic aerosols on cyclone frequency is found over the North Indian Ocean, with explained log likelihoods of 27%. A weaker but still significant impact is found for observed dust aerosols in the North Atlantic with an explained log likelihood of 11%. Changes in lower stratospheric temperatures explain 28% of the log likelihood in the North Atlantic. Lower stratospheric temperatures from a subset of Coupled Model Intercomparison Project Phase 5 models properly simulate the warming and subsequent cooling of the lower stratosphere that follows a volcanic eruption but underestimates the cooling by about 0.5°C. , Key Points Significant impact of black carbon and organic aerosols Significant impact of observed dust aerosols in the North Atlantic Lower stratospheric temperatures explain 28% of the log likelihood

Fennoscandian freshwater control on Greenland hydroclimate shifts at the onset of the Younger Dryas - Muschitiello, Francesco; Pausata, Francesco S. R.; Watson, Jenny E.; Smittenberg, Rienk H.; Salih, Abubakr A. M.; Brooks, Stephen J.; Whitehouse, Nicola J.; Karlatou-Charalampopoulou, Artemis; Wohlfarth, Barbara (Nature Communications, 2015)
Abstract Sources and timing of freshwater forcing relative to hydroclimate shifts recorded in Greenland ice cores at the onset of Younger Dryas, ∼12,800 years ago, remain speculative. Here we show that progressive Fennoscandian Ice Sheet (FIS) melting 13,100–12,880 years ago generates a hydroclimate dipole with drier–colder conditions in Northern Europe and wetter–warmer conditions in Greenland. FIS melting culminates 12,880 years ago synchronously with the start of Greenland Stadial 1 and a large-scale hydroclimate transition lasting ∼180 years. Transient climate model simulations forced with FIS freshwater reproduce the initial hydroclimate dipole through sea-ice feedbacks in the Nordic Seas. The transition is attributed to the export of excess sea ice to the subpolar North Atlantic and a subsequent southward shift of the westerly winds. We suggest that North Atlantic hydroclimate sensitivity to FIS freshwater can explain the pace and sign of shifts recorded in Greenland at the climate transition into the Younger Dryas.

The Effect of Strong Volcanic Eruptions on ENSO - McGregor, Shayne; Khodri, Myriam; Maher, Nicola; Ohba, Masamichi; Pausata, Francesco S. R.; Stevenson, Samantha (Geophysical Monograph Series, 2020)

Tropical cyclone activity enhanced by Sahara greening and reduced dust emissions during the African Humid Period - Pausata, Francesco S. R.; Emanuel, Kerry A.; Chiacchio, Marc; Diro, Gulilat T.; Zhang, Qiong; Sushama, Laxmi; Stager, J. Curt; Donnelly, Jeffrey P. (Proceedings of the National Academy of Sciences, 2017)
Significance Our modeling study shows the crucial role of vegetation cover over the Sahara and reduced dust emission in altering tropical cyclone activity during the mid-Holocene (6,000 yBP). Our results also demonstrate how these regional changes in land cover and dust emission are able to affect areas far afield through changes of large-scale atmospheric circulation. Our study strongly suggests that an appropriate representation of land cover and dust emission is of paramount importance to be able to capture past—and potentially future—climate changes. , Tropical cyclones (TCs) can have devastating socioeconomic impacts. Understanding the nature and causes of their variability is of paramount importance for society. However, historical records of TCs are too short to fully characterize such changes and paleo-sediment archives of Holocene TC activity are temporally and geographically sparse. Thus, it is of interest to apply physical modeling to understanding TC variability under different climate conditions. Here we investigate global TC activity during a warm climate state (mid-Holocene, 6,000 yBP) characterized by increased boreal summer insolation, a vegetated Sahara, and reduced dust emissions. We analyze a set of sensitivity experiments in which not only solar insolation changes are varied but also vegetation and dust concentrations. Our results show that the greening of the Sahara and reduced dust loadings lead to more favorable conditions for tropical cyclone development compared with the orbital forcing alone. In particular, the strengthening of the West African Monsoon induced by the Sahara greening triggers a change in atmospheric circulation that affects the entire tropics. Furthermore, whereas previous studies suggest lower TC activity despite stronger summer insolation and warmer sea surface temperature in the Northern Hemisphere, accounting for the Sahara greening and reduced dust concentrations leads instead to an increase of TC activity in both hemispheres, particularly over the Caribbean basin and East Coast of North America. Our study highlights the importance of regional changes in land cover and dust concentrations in affecting the potential intensity and genesis of past TCs and suggests that both factors may have appreciable influence on TC activity in a future warmer climate.

End of Green Sahara amplified mid- to late Holocene megadroughts in mainland Southeast Asia - Griffiths, Michael L.; Johnson, Kathleen R.; Pausata, Francesco S. R.; White, Joyce C.; Henderson, Gideon M.; Wood, Christopher T.; Yang, Hongying; Ersek, Vasile; Conrad, Cyler; Sekhon, Natasha (Nature Communications, 2020)
Abstract Between 5 and 4 thousand years ago, crippling megadroughts led to the disruption of ancient civilizations across parts of Africa and Asia, yet the extent of these climate extremes in mainland Southeast Asia (MSEA) has never been defined. This is despite archeological evidence showing a shift in human settlement patterns across the region during this period. We report evidence from stalagmite climate records indicating a major decrease of monsoon rainfall in MSEA during the mid- to late Holocene, coincident with African monsoon failure during the end of the Green Sahara. Through a set of modeling experiments, we show that reduced vegetation and increased dust loads during the Green Sahara termination shifted the Walker circulation eastward and cooled the Indian Ocean, causing a reduction in monsoon rainfall in MSEA. Our results indicate that vegetation-dust climate feedbacks from Sahara drying may have been the catalyst for societal shifts in MSEA via ocean-atmospheric teleconnections.

The archaeology of climate change: The case for cultural diversity - Burke, Ariane; Peros, Matthew C.; Wren, Colin D.; Pausata, Francesco S. R.; Riel-Salvatore, Julien; Moine, Olivier; De Vernal, Anne; Kageyama, Masa; Boisard, Solène (Proceedings of the National Academy of Sciences, 2021)
Anthropogenic climate change is currently driving environmental transformation on a scale and at a pace that exceeds historical records. This represents an undeniably serious challenge to existing social, political, and economic systems. Humans have successfully faced similar challenges in the past, however. The archaeological record and Earth archives offer rare opportunities to observe the complex interaction between environmental and human systems under different climate regimes and at different spatial and temporal scales. The archaeology of climate change offers opportunities to identify the factors that promoted human resilience in the past and apply the knowledge gained to the present, contributing a much-needed, long-term perspective to climate research. One of the strengths of the archaeological record is the cultural diversity it encompasses, which offers alternatives to the solutions proposed from within the Western agro-industrial complex, which might not be viable cross-culturally. While contemporary climate discourse focuses on the importance of biodiversity, we highlight the importance of cultural diversity as a source of resilience.

Initiation of a stable convective hydroclimatic regime in Central America circa 9000 years BP - Winter, Amos; Zanchettin, Davide; Lachniet, Matthew; Vieten, Rolf; Pausata, Francesco S. R.; Ljungqvist, Fredrik Charpentier; Cheng, Hai; Edwards, R. Lawrence; Miller, Thomas; Rubinetti, Sara; Rubino, Angelo; Taricco, Carla (Nature Communications, 2020)
Abstract Many Holocene hydroclimate records show rainfall changes that vary with local orbital insolation. However, some tropical regions display rainfall evolution that differs from gradual precessional pacing, suggesting that direct rainfall forcing effects were predominantly driven by sea-surface temperature thresholds or inter-ocean temperature gradients. Here we present a 12,000 yr continuous U/Th-dated precipitation record from a Guatemalan speleothem showing that Central American rainfall increased within a 2000 yr period from a persistently dry state to an active convective regime at 9000 yr BP and has remained strong thereafter. Our data suggest that the Holocene evolution of Central American rainfall was driven by exceeding a temperature threshold in the nearby tropical oceans. The sensitivity of this region to slow changes in radiative forcing is thus strongly mediated by internal dynamics acting on much faster time scales.

Hydroclimate in the Pamirs Was Driven by Changes in Precipitation‐Evaporation Seasonality Since the Last Glacial Period - Aichner, Bernhard; Makhmudov, Zafar; Rajabov, Ilhomjon; Zhang, Qiong; Pausata, Francesco S. R.; Werner, Martin; Heinecke, Liv; Kuessner, Marie L.; Feakins, Sarah J.; Sachse, Dirk; Mischke, Steffen (Geophysical Research Letters, 2019)
Abstract The Central Asian Pamir Mountains (Pamirs) are a high‐altitude region sensitive to climatic change, with only few paleoclimatic records available. To examine the glacial‐interglacial hydrological changes in the region, we analyzed the geochemical parameters of a 31‐kyr record from Lake Karakul and performed a set of experiments with climate models to interpret the results. δD values of terrestrial biomarkers showed insolation‐driven trends reflecting major shifts of water vapor sources. For aquatic biomarkers, positive δD shifts driven by changes in precipitation seasonality were observed at ca. 31–30, 28–26, and 17–14 kyr BP. Multiproxy paleoecological data and modelling results suggest that increased water availability, induced by decreased summer evaporation, triggered higher lake levels during those episodes, possibly synchronous to northern hemispheric rapid climate events. We conclude that seasonal changes in precipitation‐evaporation balance significantly influenced the hydrological state of a large waterbody such as Lake Karakul, while annual precipitation amount and inflows remained fairly constant. , Plain Language Summary Lakes in arid Central Asia are particularly susceptible to the rise and fall of lake levels as a consequence of climatic changes. To evaluate drivers behind this phenomenon, we developed a record of humidity and lake levels throughout the last 31,000 years from a high‐altitude lake in the Pamir Mountains. Herefore, we combined hydrological and ecological reconstructions with climate model experiments. Results show that neither the enhanced inflow by melting glaciers nor the significantly increased precipitation amount was responsible for higher lake levels during the studied interval. Instead, reduced summer evaporation during cold episodes was the major trigger for lake transgressions. These fluctuations were driven by changes in radiative forcing (i.e., insolation and hence temperature change) as a consequence of changes in the Earth's orbit around the Sun. As such, our results suggest that a significant impact on lake levels in arid regions is also to be expected by the current anthropogenically driven global warming. , Key Points Proxies for hydroclimate and catchment ecology show insolation‐driven trends, with higher δD values during the LGM similar to outputs from climate models Reduced summer evaporation during cold episodes increased water availability Increased summer moisture caused higher lake levels at 31–30, 28–26, and 17–14 kyr BP coinciding with northern hemispheric rapid climate events

Future Response of Temperature and Precipitation to Reduced Aerosol Emissions as Compared with Increased Greenhouse Gas Concentrations - Acosta Navarro, Juan C.; Ekman, Annica M. L.; Pausata, Francesco S. R.; Lewinschal, Anna; Varma, Vidya; Seland, Øyvind; Gauss, Michael; Iversen, Trond; Kirkevåg, Alf; Riipinen, Ilona; Hansson, Hans Christen (Journal of Climate, 2017)
Abstract Experiments with a climate model (NorESM1) were performed to isolate the effects of aerosol particles and greenhouse gases on surface temperature and precipitation in simulations of future climate. The simulations show that by 2025–49 a reduction of aerosol emissions from fossil fuels following a maximum technically feasible reduction (MFR) scenario could lead to a global and Arctic warming of 0.26 and 0.84 K, respectively, as compared with a simulation with fixed aerosol emissions at the level of 2005. If fossil fuel emissions of aerosols follow a current legislation emissions (CLE) scenario, the NorESM1 model simulations yield a nonsignificant change in global and Arctic average surface temperature as compared with aerosol emissions fixed at year 2005. The corresponding greenhouse gas effect following the representative concentration pathway 4.5 (RCP4.5) emission scenario leads to a global and Arctic warming of 0.35 and 0.94 K, respectively. The model yields a marked annual average northward shift in the intertropical convergence zone with decreasing aerosol emissions and subsequent warming of the Northern Hemisphere. The shift is most pronounced in the MFR scenario but also visible in the CLE scenario. The modeled temperature response to a change in greenhouse gas concentrations is relatively symmetric between the hemispheres, and there is no marked shift in the annual average position of the intertropical convergence zone. The strong reduction in aerosol emissions in the MFR scenario also leads to a net southward cross-hemispheric energy transport anomaly both in the atmosphere and ocean, and enhanced monsoon circulation in Southeast Asia and East Asia causing an increase in precipitation over a large part of this region.

Sensitivity of northwest Australian tropical cyclone activity to ITCZ migration since 500 CE - Denniston, Rhawn F.; Ummenhofer, Caroline C.; Emanuel, Kerry; Ingrosso, Roberto; Pausata, Francesco S. R.; Wanamaker, Alan D.; Lachniet, Matthew S.; Carr, Kenneth T.; Asmerom, Yemane; Polyak, Victor J.; Nott, Jonathan; Zhang, Wei; et al. (Science Advances, 2023)
Tropical cyclones (TCs) regularly form in association with the intertropical convergence zone (ITCZ), and thus, its positioning has implications for global TC activity. While the poleward extent of the ITCZ has varied markedly over past centuries, the sensitivity with which TCs responded remains poorly understood from the proxy record, particularly in the Southern Hemisphere. Here, we present a high-resolution, composite stalagmite record of ITCZ migrations over tropical Australia for the past 1500 years. When integrated with a TC reconstruction from the Australian subtropics, this time series, along with downscaled climate model simulations, provides an unprecedented examination of the dependence of subtropical TC activity on meridional shifts in the ITCZ. TCs tracked the ITCZ at multidecadal to centennial scales, with a more southward position enhancing TC-derived rainfall in the subtropics. TCs may play an increasingly important role in Western Australia’s moisture budgets as subtropical aridity increases due to anthropogenic warming. , Stalagmites and climate models reveal ITCZ shifts drove concurrent changes in Australian tropical cyclone and monsoon rainfall.

Development and testing scenarios for implementing land use and land cover changes during the Holocene in Earth system model experiments - Harrison, Sandy P.; Gaillard, Marie-José; Stocker, Benjamin D.; Vander Linden, Marc; Klein Goldewijk, Kees; Boles, Oliver; Braconnot, Pascale; Dawson, Andria; Fluet-Chouinard, Etienne; Kaplan, Jed O.; Kastner, Thomas; Pausata, Francesco S. R.; et al. (Geoscientific Model Development, 2020)
Abstract. Anthropogenic changes in land use and land cover (LULC) during the pre-industrial Holocene could have affected regional and global climate. Existing scenarios of LULC changes during the Holocene are based on relatively simple assumptions and highly uncertain estimates of population changes through time. Archaeological and palaeoenvironmental reconstructions have the potential to refine these assumptions and estimates. The Past Global Changes (PAGES) LandCover6k initiative is working towards improved reconstructions of LULC globally. In this paper, we document the types of archaeological data that are being collated and how they will be used to improve LULC reconstructions. Given the large methodological uncertainties involved, both in reconstructing LULC from the archaeological data and in implementing these reconstructions into global scenarios of LULC, we propose a protocol to evaluate the revised scenarios using independent pollen-based reconstructions of land cover and climate. Further evaluation of the revised scenarios involves carbon cycle model simulations to determine whether the LULC reconstructions are consistent with constraints provided by ice core records of CO2 evolution and modern-day LULC. Finally, the protocol outlines how the improved LULC reconstructions will be used in palaeoclimate simulations in the Palaeoclimate Modelling Intercomparison Project to quantify the magnitude of anthropogenic impacts on climate through time and ultimately to improve the realism of Holocene climate simulations.

Deciphering local and regional hydroclimate resolves contradicting evidence on the Asian monsoon evolution - Wolf, Annabel; Ersek, Vasile; Braun, Tobias; French, Amanda D.; McGee, David; Bernasconi, Stefano M.; Skiba, Vanessa; Griffiths, Michael L.; Johnson, Kathleen R.; Fohlmeister, Jens; Breitenbach, Sebastian F. M.; Pausata, Francesco S. R.; et al. (Nature Communications, 2023)
Abstract The winter and summer monsoons in Southeast Asia are important but highly variable sources of rainfall. Current understanding of the winter monsoon is limited by conflicting proxy observations, resulting from the decoupling of regional atmospheric circulation patterns and local rainfall dynamics. These signals are difficult to decipher in paleoclimate reconstructions. Here, we present a winter monsoon speleothem record from Southeast Asia covering the Holocene and find that winter and summer rainfall changed synchronously, forced by changes in the Pacific and Indian Oceans. In contrast, regional atmospheric circulation shows an inverse relation between winter and summer controlled by seasonal insolation over the Northern Hemisphere. We show that disentangling the local and regional signal in paleoclimate reconstructions is crucial in understanding and projecting winter and summer monsoon variability in Southeast Asia.

The Model Intercomparison Project on the climatic response toVolcanic forcing (VolMIP): experimental design and forcing input data for CMIP6 - Zanchettin, Davide; Khodri, Myriam; Timmreck, Claudia; Toohey, Matthew; Schmidt, Anja; Gerber, Edwin P.; Hegerl, Gabriele; Robock, Alan; Pausata, Francesco S. R.; Ball, William T.; Bauer, Susanne E.; Bekki, Slimane; et al. (Geoscientific Model Development, 2016)
Abstract. The enhancement of the stratospheric aerosol layer by volcanic eruptions induces a complex set of responses causing global and regional climate effects on a broad range of timescales. Uncertainties exist regarding the climatic response to strong volcanic forcing identified in coupled climate simulations that contributed to the fifth phase of the Coupled Model Intercomparison Project (CMIP5). In order to better understand the sources of these model diversities, the Model Intercomparison Project on the climatic response to Volcanic forcing (VolMIP) has defined a coordinated set of idealized volcanic perturbation experiments to be carried out in alignment with the CMIP6 protocol. VolMIP provides a common stratospheric aerosol data set for each experiment to minimize differences in the applied volcanic forcing. It defines a set of initial conditions to assess how internal climate variability contributes to determining the response. VolMIP will assess to what extent volcanically forced responses of the coupled ocean–atmosphere system are robustly simulated by state-of-the-art coupled climate models and identify the causes that limit robust simulated behavior, especially differences in the treatment of physical processes. This paper illustrates the design of the idealized volcanic perturbation experiments in the VolMIP protocol and describes the common aerosol forcing input data sets to be used.

The PMIP4 contribution to CMIP6 – Part 2: Two interglacials, scientific objective and experimental design for Holocene and Last Interglacial simulations - Otto-Bliesner, Bette L.; Braconnot, Pascale; Harrison, Sandy P.; Lunt, Daniel J.; Abe-Ouchi, Ayako; Albani, Samuel; Bartlein, Patrick J.; Capron, Emilie; Carlson, Anders E.; Dutton, Andrea; Fischer, Hubertus; Goelzer, Heiko; et al. (Geoscientific Model Development, 2017)
Abstract. Two interglacial epochs are included in the suite of Paleoclimate Modeling Intercomparison Project (PMIP4) simulations in the Coupled Model Intercomparison Project (CMIP6). The experimental protocols for simulations of the mid-Holocene (midHolocene, 6000 years before present) and the Last Interglacial (lig127k, 127 000 years before present) are described here. These equilibrium simulations are designed to examine the impact of changes in orbital forcing at times when atmospheric greenhouse gas levels were similar to those of the preindustrial period and the continental configurations were almost identical to modern ones. These simulations test our understanding of the interplay between radiative forcing and atmospheric circulation, and the connections among large-scale and regional climate changes giving rise to phenomena such as land–sea contrast and high-latitude amplification in temperature changes, and responses of the monsoons, as compared to today. They also provide an opportunity, through carefully designed additional sensitivity experiments, to quantify the strength of atmosphere, ocean, cryosphere, and land-surface feedbacks. Sensitivity experiments are proposed to investigate the role of freshwater forcing in triggering abrupt climate changes within interglacial epochs. These feedback experiments naturally lead to a focus on climate evolution during interglacial periods, which will be examined through transient experiments. Analyses of the sensitivity simulations will also focus on interactions between extratropical and tropical circulation, and the relationship between changes in mean climate state and climate variability on annual to multi-decadal timescales. The comparative abundance of paleoenvironmental data and of quantitative climate reconstructions for the Holocene and Last Interglacial make these two epochs ideal candidates for systematic evaluation of model performance, and such comparisons will shed new light on the importance of external feedbacks (e.g., vegetation, dust) and the ability of state-of-the-art models to simulate climate changes realistically.